Medico-Legal Issues in Air Gun Injuries - Gunethilake, K.; Vidanapathirana, M. (IOSR Journal of Dental and Medical Sciences (IOSR-JDMS), 2016)
Attached

Introduction: The only difference of airgun with rest of firearms is it propels projectile by means of compressed air. Air gun injuries are uncommon in Sri Lanka as it is not commonly used. However, it seems to be promoting since recently. There are no laws related to air guns and anybody can buy for the purpose of hunting and a license is not needed. Case report: An 8 year old boy was admitted with an injury to the right hand. According to father, the injury was due to an accidental fall. There was a circular shape 3 mm perforated laceration with 5 mm abraded margin at the base of right palm. However, there were no evidence of burning, blackening or tattooing. X-ray examination revealed a dumbbell shaped radio-opaque foreign body in the right wrist damaging the epiphysis of the radius. A metallic foreign body was surgically removed. Later, it was revealed that the child received injuries while playing with one of his relative children with an air gun. Conclusions: The findings were compatible with injuries caused by an air gun. Although air guns can be used in meaningful manner, it is dangerous in children’s hands. Though no reported fatal cases in Sri Lanka, they can be modified and use for dangerous purposes. Therefore, it is recommended to develop regulations and control on air guns
Keywords: Air guns; injuries; regulations